Dyskurs żalu czy ulgi? Wałbrzych w dwadzieścia lat po zamknięciu kopalń (Politeja, 2017)
The Discourse of Regret or Relief? Wałbrzych Twenty Years After the Closure of the MinesThe paper presents the results of field research carried out in 2015 in Wałbrzych, focused on as well memory as arising postmemory of citizens, clustered around the closure of all coal mines in the 1990s. For citizens of Wałbrzych their failure was liminal situation and memory about it is still alive and constitutes significant element of identity. Memory of this social trauma and civilizational collapse is passed down from one generation to the next and also has impact on those who were not personally affected by it. The narratives established around the liquidation of the coal mines are split and often contrary. On the one hand the work in the mine was considered positively (primarily because of the financial benefits and social respect), but on the other hand poor working conditions were emphasized. Respondents remembered about dangerousness of the work in mine (therefore relief discourse), but at the same time they criticized decision about the closure of coal mines (therefore resentment discourse).